2004
DOI: 10.1136/emj.2002.003665
|View full text |Cite
|
Sign up to set email alerts
|

Team triage improves emergency department efficiency

Abstract: Objective: To see whether three hours of combined doctor and nurse triage would lead to earlier medical assessment and treatment and whether this benefit would carry on for the rest of the day when normal triage had resumed. Method: Eight days were randomly selected; four for team triage and four for the normal nurse led triage. Team triage was coordinated by a middle grade or consultant from 9 am to 12 noon. Times to triage, to see a doctor, radiology, admission, and discharge were recorded. No additional med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 5 publications
1
85
1
2
Order By: Relevance
“…Team-training exercises for health care professionals are considered to be a highly effective tool to improve communication and team performance, particularly in crisis situations. [8][9][10] TeamSTEPPS, developed by the Department of Defense and the AHRQ, is an evidence-based framework to optimize team performance across the health care delivery system. 11,12 The framework comprises 4 teaching and learning skills: (1) leadership, (2) situation monitoring, (3) mutual support, and (4) communication.…”
Section: Discussionmentioning
confidence: 99%
“…Team-training exercises for health care professionals are considered to be a highly effective tool to improve communication and team performance, particularly in crisis situations. [8][9][10] TeamSTEPPS, developed by the Department of Defense and the AHRQ, is an evidence-based framework to optimize team performance across the health care delivery system. 11,12 The framework comprises 4 teaching and learning skills: (1) leadership, (2) situation monitoring, (3) mutual support, and (4) communication.…”
Section: Discussionmentioning
confidence: 99%
“…In three similar models to the research site, Han et al [4] , Partovi et al [5] , and Holroyd et al [6] showed a reduction in overall LOS and number of patients leaving without being seen (LWBS). In two studies from the United Kingdom, Terris et al [7] noted a reduction in number of patients waiting to be seen at any one time utilizing a physician in triage while Subash et al [10] showed that team triage for three hours a day reduced time to see a doctor and time to radiology during the time of intervention but not for the remainder of the day. Finally, in a study from Hong Kong, Choi et al [8] showed a reduction in mean waiting time and mean processing time by moving a faculty to triage without additional staffing.…”
Section: Discussionmentioning
confidence: 99%
“…studies in the literature that have investigated the use of a physician in triage [4][5][6][7][8][9][10][11][12] . The majority of these studies have focused on patient flow metrics for measured outcomes.…”
mentioning
confidence: 99%
“…However, previous studies have shown that physician triage improves ED LOS and may bias our findings toward an improvement in ambulance diversion and ED LOS. [21][22][23] Physician triage may also explain why our left-without-being-seen rates decreased slightly. 21 Our study did not account for seasonal variation.…”
Section: Limitationsmentioning
confidence: 99%